Recent Progress in the Research of Eosinophilic Esophagitis and Gastroenteritis - Kinoshita, Yoshikazu; Ishimura, Norihisa; Oshima, Naoki; Mikami, Hironobu; Okimoto, Eiko; Jiao, Di Jin; Ishihara, Shunji (Digestion, 2016)
Eosinophilic esophagitis (EoE) and gastroenteritis are allergic gastrointestinal diseases mainly caused by food allergens. The number of patients with EoE is rapidly increasing in both Western and Asian countries. Basic knowledge of these diseases has mainly come from studies of EoE and Th2 type allergic reactions, including IL-5, IL-13, and IL-15, thymic stromal protein, and eotaxin 3, which are considered to have important roles. For a diagnosis of EoE, endoscopic abnormalities and histological confirmation of dense eosinophile infiltration in the esophageal epithelial layer are important, in addition to identifying dysphagia symptoms. As for eosinophilic gastroenteritis, blood test findings are more useful and the role of an endoscopic examination is reduced. For both diseases, the infection rate of Helicobacter pylori is lower than in healthy controls. Glucocorticoid administration is standard treatment for these diseases, while proton pump inhibitors are frequently effective for EoE.